A Multivariate Model of Strategic Asset Allocation with Longevity Risk. (31st October 2017) - Bisetti, Emilio; Favero, Carlo A.; Nocera, Giacomo; Tebaldi, Claudio
Abstract : Population-wide increase in life expectancy is a source of aggregate risk. Longevity-linked securities are a natural instrument to reallocate that risk. This paper extends the standard Campbell–Viceira (2005 ) strategic asset allocation model by including a longevity-linked investment possibility. Model estimation, based on prices for standardized annuities publicly offered by U.S. insurance companies, shows that aggregate shocks to survival probabilities are predictors for long-term returns of the longevity-linked securities, and reveals an unexpected predictability pattern. Valuation of longevity risk premium confirms that longevity-linked securities offer inexpensive funding opportunities to asset managers.